Reaching out: help-seeking among professional male ice hockey athletes - Crawford, K. L.; Wilson, B.; Hurd, L.; Beauchamp, M. R. (Qualitative Research in Sport, Exercise and Health, 2023)
The purpose of this study was to explore male ice hockey athletes` experiences with barriers and facilitators to asking for help while competing in professional leagues (e.g. National Hockey League). Using a critical interpretivist approach, we conducted semi-structured interviews with 19 athletes (aged 24-41 years), who either held a professional contract or recently retired from professional ice hockey within five years of the interview. The data were thematically analysed whereby four overarching themes and 19 subthemes were identified to reflect the various barriers to, and facilitators of, athlete help- seeking. The themes included (1) cultural norms: old versus new school (2) culturally informed identities, (3) personal agency, and (4) provision of resources. The first theme reflects how tensions between old and new school cultural norms promote and/or restrict help-seeking. The second theme encompasses how participants described their sense of self, as linked to help-seeking within the context of professional ice hockey. The third theme details how participants perceived their help-seeking literacy, autonomy, maturity, and personal mindset to facilitate or restrict help-seeking. The final theme corresponded to how the quality of the resources and relationships with support personnel facilitated or created barriers to help-seeking. The results indicate that the culture of professional ice hockey is highly influential in terms of how athletes understand and frame help-seeking behaviours and, in turn, how they engage in help-seeking behaviours. The findings further highlight potential means through which key social agents (e.g. coaches, psychologists, general managers) can reduce barriers and facilitate athlete help-seeking.